Wilms tumor in adult - Karim, ME; Momen, MA; Akhter, S; Haque, Z; Islam, T; Haque, MM; Hossain, M (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):299-302. The abstract of this article is available on the PubMed website